The role of the size and growth rate of the bank in determining the effect of financial leverage on the profitability of Jordanian commercial banks - AL-Shatnawi, Hasan Mahmoud; Hamawandy, Nawzad Majeed; Sharif, Rahim Jafar Mahammad; jaf, Rizgar Abdullah Sabir; Al-Kake, Farhad (The journal of contemporary issues in business and government, 2021)
This study aims to determine the role of the size and growth rate of banks in determining the effect of the financial leverage degree on the profitability of Jordanian commercial banks. To achieve this goal, the study adopted the analytical descriptive research approach and analysed the financial reports of 13 Jordanian commercial banks listed on the Amman Stock Exchange Market (ASEM) during 2014–2018. To test the hypotheses and achieve the study goal, the data were analysed using simple linear regression analysis and hierarchical interaction regression analysis. The analyses showed that there is a positive effect on the financial leverage degree on the profitability of Jordanian commercial banks. Moreover, the results uncovered that the interaction effects of the financial leverage degree and the size and the growth rate of the bank foster the positive effects of the individual variables on the profitability of the banks. foreign direct investments is also the essential ingredient to the growth and development of most economies (Baban & Hasan, 2019). The most important factors in the economic growth processing of any country are the commercial transactions and foreign direct investments (Adl.Nawzad, 2020). The element of knowledge management and innovation are currently considered as integral in all aspects and operations of an organization given the fact that they determine the survival of entities in the corporate market (Jabbar et al., 2019).